A comparative study of the clinical efficacy and quality of life of modified Brisson surgery vs traditional Devine surgery in the treatment of concealed penis - Guo, Na; Yang, Bin; Li, Nan; Wang, Yi; Chen, Haitao (Frontiers in Surgery, 2025)
ObjectiveThis study aims to compare and analyze the differences in clinical efficacy and quality of life between the modified Brisson surgery and the traditional Devine surgery for the treatment of concealed penis (CP).MethodsThis comparative study recruited 120 children with CP admitted to Baoding Hospital, Beijing Children's Hospital Affiliated to Capital Medical University, from March 2023 to July 2024. The patients were randomly divided into two groups: the experimental group and the control group, with 60 cases in each group. The experimental group received the modified Brisson surgery, while the control group received the traditional Devine surgery. The surgical outcomes, penile length before and after surgery, incidence of postoperative complications, and changes in quality of life were compared and analyzed between the two groups.ResultsThe response rate in the experimental group was 100%, which was significantly higher than that in the control group (93%), with a statistically significant difference (P = 0.02). At 6 months after surgery, the penile length in the experimental group was significantly longer than that in the control group (P < 0.001). The incidence of surgical complications was 5% in the experimental group and 17% in the control group, with a statistically significant difference (P = 0.03). Moreover, after intervention, the experimental group had significantly higher scores in indexes such as convenience of life, somatic feeling, negative emotion, self-concept, peer relationship, and self-satisfaction compared with the control group (P < 0.001).ConclusionThe modified Brisson surgery offers several advantages in the treatment of CP, including good treatment outcomes, a high response rate, a low postoperative complication rate, and significant improvements in quality of life indicators. These benefits make it a valuable approach worthy of promotion in clinical practice.